Artificial Intelligence in Healthcare: A New Technology Benefit for Both Patients and Doctors - Sharma, Dharmendra (Digital Repository of Theses - SSBM Geneva, 2025)
Artificial Intelligence (AI) is a frontrunner medical technology with unparalleled medical diagnosis, care for patients, and process automation. Safety and ethics considerations pertinent to the rapid adoption of AI in healthcare environments exist. These are covered in this paper and offer an understanding of healthcare providers, current regulations, and emerging adaptive evaluation systems to support safe AI deployment. The research utilizes the mixed-methods approach, quantitative survey and qualitative expert interviews, to provide an in-depth examination of AI ethics. A systematic literature review was utilized to analyze and critique empirical studies on some risks of AI including data privacy, algorithmic bias, informed consent, and sufficiency of current policies that span AI. The quantitative part of the study entailed a systematic questionnaire that was sent to healthcare professionals, AI developers, and policymakers and gathered their opinions on the benefits, risks, and ethics of AI. The qualitative part included stakeholder workshops and semi-structured interviews that gathered in-depth insights on real-world problems and solutions for the effective use of AI in healthcare. The research has impactful results which are a growing concern to practitioners that AI undermines patient independence, increases data vulnerability, and comes with bias in healthcare decision- making. The findings also indicate that with more knowledge about AI people are more ethically engaged, which warrants the establishment of stand-alone AI literacy modules. The research also identifies loopholes in the regulation, confirming that current AI-regulating infrastructures fall short as long as they do not take into account the entire range of ethical and security threats. In consideration of these findings, the study prescribes adaptive guidelines for discussion about making utmost priority toward real-time observation, transparency, and interdisciplinarity between regulators, AI designers, and healthcare practitioners. These tend to fill gaps between needs in regulation and safeguarding measures and ethics compliance towards AI innovation to ensure the use of AI technology within healthcare is tolerable. The results of the study transcend theoretical and practical uses. Theoretically, the research advances AI ethics literature because it situates the intersectionality of AI knowledge and its respective ethical consequences. Practically, it advocates for proper AI training for physicians, real-time monitoring platforms for AI, and policy reform for strengthening the regulation of AI. Although the research provides rich insights, it also leads to areas of research such as longitudinal study of the effect of AI on patient outcomes, comparative analysis of US-style regulation of AI in healthcare systems across nations, and attitudes of patients towards AI-based health interventions. The research puts stress on adopting a strong value-based approach to the adoption of AI in healthcare to ensure that technological advancements will be patient-centric, data-proof, and regulatory compliant. With the integrated solution of AI integration's safety and ethical concerns, this thesis offers a basis for ethical regulation of AI to facilitate policymakers, healthcare facilities, and powerful AI providers in AI-integrated healthcare.